Uncovering children reception towards children television programme in Malaysia / Shazleen Mohamed - Mohamed, Shazleen (Institute of Graduate Studies, UiTM, 2018)
This study is endeavoring to uncover the children reception towards children television programme in Malaysia. The study concentrated on five research objectives: (i) to identify how children express their preferences towards the television programmes (ii) to unravel how the children respond towards the television programmes they watched (iii) to reveal how children interpret the social reality and fantasies of the scenes in the television programmes they watched (iv) to determine how children identify themselves with the characters in the television programmes they watched and (v) to uncover how children being influenced in term of cognitive, affective and behavior by the television programmes they watch. This study does not attempt to observe if television has effects on children. 30 children aged between four to six years old were interviewed and observed in the study. Interviews were conducted in both English and Malay depending on the language in which the children were best able to express themselves: some were bi-lingual and some spoke only Malay. During the course of observations, the researchers watched and recorded everything the children said and did while they were viewing. Firstly, irrespective of their ages (four, five or six years old), the children managed to identify and determine what program that they like to watch. The children express their preferences based on these characteristics (i) for fun (ii) for relaxation and comfort (iii) to avoid boredom and (iv) to bond with parents and siblings…